Analisis Implementasi Fitur Prepopulated Pajak Masukan dalam Pelaporan SPT Masa PPN Menggunakan Aplikasi E-Faktur 3.0 dan E-Faktur Web Based (Studi Kasus pada PT Lancar Agung Abadi Tahun 2021) - Aisyah Prasetiawati; Mainita Hidayati (Jurnal Ilmu Administrasi Publik, 2022)
This study was motivated by the existence of Taxpayers who do not know the benefits of using the Prepopulated Feature and how the implementation of the Input Tax Prepopulated Feature in reporting the VAT return at PT Lancar Agung Abadi can run well and effectively. The research method used in this study was a qualitative approach with descriptive research type. The results showed that the implementation of the Prepopulated Feature, although from a technical point of view still has obstacles, but the overall implementation has gone well, this can be seen from the many benefits of using the feature. The procedure for using the prepopulated feature is clear enough for PT Lancar Agung Abadi. Socializations have been held such as in seminars through zoom meetings regarding e-faktur updates and the use of the latest features. The resources have been very helpful for PT Lancar Agung Abadi. The disposition of the implementers strongly supports the application of this feature because it is considered to have many benefits. The bureaucratic structure regarding the availability of clear rules regarding duties and responsibilities is in accordance with its Main Duties and Functions. The obstacle faced is the system errors that often occur due to the overload of the use of the E-faktur system. The solution is to repair internet network disturbances and report taxes earlier a few days before the end of the tax period